Wayside School gets a little stranger - Sachar, Louis, 1954-; Schick, Joel (New York : Morrow Junior Books, 1995)
Unusual things continue to happen in the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
Wilson's Children, October 2010.
School Library Journal, April 1995.
Book Links (A.L.A.), May 2006.
Child Study Children's Book Committee, January 1996.
Publisher's Weekly, March 1996.
Bulletin (Center for Children's books), March 1995.
Keywords: Schools -- Fiction; Humorous stories; School stories; Humorous fiction; Schools -- Fiction; Humorous stories